Increasing the Vase Life of Chrysanthemum Cut Flowers by Using Silver and Zinc Nanoparticles - Sulusi Prabawati; Noveria Sjafrina; Anna Sulistyaningrum; Eka Rahayu; Siti Mariana Widayanti; null Waryat; Noor Roufiq Ahmadi; Fitri Rachmawati; Abdullah Bin Arif (The Scientific World Journal)
Cut flowers are horticultural products that have great potential to be developed. Efforts to maintain quality and extend the shelf life of cut flowers are very important to obtain a product that is accepted in the market. The main problems of chrysanthemum cut flowers are the leaves easily turning yellow, wilting, and failure to fully open flowers. This study aimed to obtain the best pulsing solution formulation that increases vase life and maintains the freshness of chrysanthemum cut flowers. Pulsing solution treatment was carried out on chrysanthemum cut flowers during the evaluation period. Pulsing solution treatment consisted of control, AgNO3, nano-Ag (NAg), ZnO, and nano-Zn (NZn). The results showed that NAg20 treatment increased the vase life of chrysanthemum cut flowers up to 23 days, which was 19 days longer than the control. Nano-Ag inhibits bacterial growth, flower wilting, color degradation, and carotenoids. In addition, nano-Ag increased the size of the bloom-flower diameter. Considering the results of all postharvest quality parameters mentioned above, NAg20 extends the vase life of chrysanthemum cut flowers.